FeSTEM community platform: creating meaningful, mentoring relationships with experts in STEM - Pallaris, George; Parmaxi, Antigoni; Christou, Eirini (My University, 2021)
This poster presents an overview of an e-mentoring platform that aims to link Higher Education (HE) students in Science Technology Engineering and Mathematics (STEM) with experienced mentors in the field. Given the nature of this venture, we democratized the design process, encouraging for multiple voices from different stakeholders to be heard and inform the design process. This poster demonstrates the process adopted for building FeSTEM (Female Empowerment in Science Technology Engineering and Mathematics) e-mentoring platform and concludes with implications for research and practice in maximizing users’ involvement in the design process.
Keywords: STEM; gender equality